Pengaruh Institutional Investor Terhadap Perusahaan Jasa - Farah Margaretha; Qorrie Aina Nizar (Universitas Airlangga, 2009)
The study`s purpose is to acknowledge the factors that influence the institutional investor. The samples are service industries included Transportation, Bank, Insurance, Hotel & Travel Services, and Real Estate & Property which listed in Indonesian Stock Exchange (BEI) for the period of 2002 up to 2007. Independent variables in this study included Variable Firm Size, Capital expenditure to asset, Debt ratio, Book to market value of asset, Dividend Per Share (Turnover), Risk (Volatility), Return On Assets (ROA), Momentum, and price. Meanwhile, dependent variable is Institutional Investor. With using purposive sampling, the total of sample in this study is 18 of industries. Data analysis model are classic assumption test, regression and t-test. Based on t-test, the result of Variable Firm Size, Capital expenditure to asset, Debt ratio, Book to market value of asset, Dividend Per Share (Turnover), Risk (Volatility), Momentum, and price did not has related to Institutional Investor. Capital expenditure to asset and Return on asset (ROA) has related to Institutional Investor. To Manager Finance, result of this research is expected can become company consideration in the field of service in determining factors to draw Investor Institutional.